Iatrogenic subcutaneous metastasis from WHO Grade I intracranial meningioma. (December 2018) - Kok, David L.; Hendry, Shona; Alvarez, Beatriz
Highlights: This is a case of a WHO Grade I meningioma excised in an uncomplicated operation. 13 months later the patient presented with subcutaneous metastases. Proximity was close to her original scar, suggesting intra-operative seeding. Risk factors and treatment options for this rare occurrence are reviewed. Abstract: Meningiomas are the most frequent primary brain tumours and are often managed with surgical excision. We present the case of a young woman with the unusual phenomenon of iatrogenic subcutaneous seeding from an intracranial meningioma. We discuss the risk factors, possible mechanisms and management of this.